Zakir Naik‘s techniques in comparative theological discourse: some reflections - Aminul Islam, Mohammad; Ushama, Thameem (IIUM Press, 2022)
Zakir Naik is one of the scholars in Comparative Religion. Providing quotations with exact references from his instant memory, Naik makes his audience astonished and spellbound. In adopting a descriptive methodology, this research has attempted to explore the secrets behind Zakir Naik‘s effort in daʿwah and his techniques for preparing daʿwah materials, memorizing and delivering them to his audience. An interview has been taken to examine them accordingly. Some of the contents of this research have been collected from the interview, and the rest of the materials were studied from unpublished research done by Zakir Naik, especially daʿwah materials related to International Daʿwah Training Program in 2016. Finally, the study has attempted to offer a set of guidelines that would help create successors of Zakir Naik that may contribute to constructing a tolerant religious pluralist society.